EMPLOYEE ENGAGEMENT: TURN OVER PREVENTION STRATEGIES AND THE KEY TO IMPROVING PERFORMANCE MANAGEMENT IN A MULTINATIONAL COMPANY - Naik Henokh Parmenas (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2022)
The purpose of this study is to prevent turnover and the key to improving performance management in a multinational company. Employee engagement is believed will enable the success for a company through several people factor such as employee performance, productivity, work safety, attendance and retention, customer satisfaction, customer loyalty, to profitability. Employee performance is one of the benefits that is resulted from a high employee engagement. Factors that affect employee engagement: Work Environment (work environment), Leadership (leadership), Team and Co-worker (team and co-worker relations), Training and Career Development (training and career) Compensation (compensation), Organizational Policies, procedures, structures and systems (organizational policies, procedures, structures, and systems), Workplace well-being (work welfare). This research method is a literature study by comparing several existing theories, previous research, and interviews with several sources in several multinational companies. The findings are still high in the company's annual turnover rate. From this research, it can be concluded that employee engagement programs must be carried out regularly in a company organization so that employees are loyal to management.